Quality of Sleep in an HIV Population on Antiretroviral Therapy at an Urban Tertiary Centre in Lagos, Nigeria - Olajumoke Oshinaike; Akinsegun Akinbami; Olaitan Ojelabi; Akinola Dada; Adedoyin Dosunmu; Sarah John Olabode (Neurology Research International)
Aim. To determine the prevalence of sleep disturbance and its associated characteristics in HIV-positive outpatients on HAART using the PSQI. Methods. Using a cross-sectional design, 300 patients attending the outpatient HIV/AIDS clinic at the Lagos State University Teaching Hospital were recruited. Baseline data obtained included the participants’ demographic data, educational qualification, and marital status. Their treatment history, including duration since HIV diagnosis, the most recent CD4 cell count, and current antiretroviral therapies, was obtained from their case records. Each participant completed the PSQI questionnaire and those with scores ≥5 were diagnosed with poor sleep quality. Results. The participants were made up of 70.7% females and 29.3% males. Their ages ranged between 18 and 74 years with a mean of 38.9±10.3 years. According to the PSQI, 59.3% reported poor sleep quality. The mean score of those with poor quality sleep (9.2±3.3) was comparable to that of those with good quality sleep (1.26±1.4). P<0.001. Significant differences were observed in all the individual components of the PSQI (P<0.001). On multivariate analyses, the independent associations with sleep quality were the duration since HIV diagnosis (P=0.29), efavirenz based regimen (P<0.001), and lower CD4 cell count (P<0.001). Conclusions. Sleep disturbances are quite common in the HIV population even in the era of HAART. Early recognition via routine assessment and effective treatments could prevent the resultant complications and improve quality of life.